Tertiary Lymphoid Structures in the Central Nervous System: Implications for Glioblastoma - van de Walle, Tiarne; Vaccaro, Alessandra; Ramachandran, Mohanraj; Pietilä, Ilkka; Essand, Magnus; Dimberg, Anna (Frontiers in Immunology, 2021)
Glioblastoma is the most common and aggressive brain tumor, which is uniformly lethal due to its extreme invasiveness and the absence of curative therapies. Immune checkpoint inhibitors have not yet proven efficacious for glioblastoma patients, due in part to the low prevalence of tumor-reactive T cells within the tumor microenvironment. The priming of tumor-directed T cells in the cervical lymph nodes is complicated by the shortage of dendritic cells and lack of appropriate lymphatic vessels within the brain parenchyma. However, recent data suggest that naive T cells may also be primed within brain tumor-associated tertiary lymphoid structures. Here, we review the current understanding of the formation of these structures within the central nervous system, and hypothesize that promotion of tertiary lymphoid structures could enhance priming of tumor-targeted T cells and sensitize glioblastomas to cancer immunotherapy.